ACTIVITY OF CLOVE LEAVES (Syzygium aromaticum L.) LARVACIDES ON MORTALITY OF Anopheles sp. - Sapulette, Fenska Violenta; Unitly, Adrien Jems Akiles; Moniharapon, Debby (Universitas Pattimura, 2019)
This study used a completely randomized design with a sample of 525 Anopheles sp. larvae. which were divided into 7 groups and 3 replicates, which contained 25 Anopheles spper larvae. Except for the control, each group was given clove leaf infusion starting from a concentration of 0.50%, 1%, 2%, 4% and 6%, where the treatment was carried out for 24 hours. The results showed that there was a larvicidal effect of brewing clove leaves (Syzygium aromaticum L.) on the mortality of Anopheles sp mosquito larvae, where the effective concentration was 6% and had an LC50 value in killing Anopheles sp larvae of 0.89%. The overall phytochemical content of clove leaves which has a fast response to the mortality of Anopheles sp. are saponins, flavonoids and tannins which are capable of acting as larvicides through the mechanism of damaging cell membranes or interfering with larval metabolic processes. The content of saponins, flavonoids and tannins can increase the mortality of Aedes aegypti L. larvae through the mechanism of damaging cell membranes or interfering with larval metabolic processes as stomach poisoning.